Study on the structure–activity relationship between the molecular structure of anionic Gemini surfactants and the rheological properties of their micelle solutions. Issue 4 (15th March 2022) - Hu, Ruizhi; Tang, Shanfa; Mpelwa, Musa; Jin, Lijun; Jiang, Zhaowen; Feng, Shuyun; Zheng, Yahui
Abstract: In this study, the viscosity and viscoelasticity of Gemini surfactant solutions with different molecular structures were measured, and the micelle structure formed by self-assembly in the solution was observed and measured using FESEM and DLS. The effect of the molecular structure of anionic Gemini surfactants on the rheological properties of the solution was studied systematically. The experimental results showed that the carboxylate Gemini surfactants with long hydrophobic carbon chains and a moderate spacer group have better rheological properties in aqueous solution. The carboxylate Gemini surfactant solution aggregated to form more densely, larger-sized micelle structures than the sulfonate Gemini surfactant, so its viscosity and viscoelasticity are greater. When the carbon number of the spacer group was the same (s = 2), as the carbon number of the hydrophobic chain increased (m = 14, 16, 18), the hydrodynamic diameter increased, the size of the micelle structures formed by self-assembly in the solution increased, the micelles aggregated more tightly, and the solution viscosity and viscoelasticity increased. When the carbon number of the hydrophobic chain was the same (m = 18), as the carbon number of the spacer group increased (s = 2, 3, 4), the hydrodynamic diameter first increased and then decreased, the micelle structures exhibited the phenomenon of aggregation first and then disintegration, and the solution viscosity and viscoelasticity also increased first and then later decreased. These phenomena indicated that the change of Gemini surfactant molecular structure would lead to the change of its micelle microstructure and eventually lead to the change of solution rheological properties. Graphical Abstract: UF0001